Longitudinal Growth Outcomes Following First-line Treatment for Pediatric Patients With Eosinophilic Esophagitis. Issue 1 (January 2019) - Jensen, Elizabeth T.; Huang, Kevin Z.; Chen, Hannah X.; Landes, Lisa E.; McConnell, Kristen A.; Almond, Mary Angie; Safta, Anca M.; Johnston, Douglas T.; Durban, Raquel; Jobe, Laura; Frost, Carrie; Donnelly, Sarah; et al.
ABSTRACT: Objectives: No formal comparative effectiveness studies have been conducted to evaluate the effect of eosinophilic esophagitis (EoE) treatment choice on long-term growth in pediatric patients. Long-term studies of inhaled corticoid steroids in asthma, however, suggest possible effects on linear growth. The aim of this study was to compare longitudinal, anthropometric growth in children with EoE according to treatment approach. Methods: We conducted a retrospective, multicenter cohort study of anthropometric growth (height and body mass index [BMI] z scores) in pediatric (<18 years of age) patients newly diagnosed with EoE across 5 clinical sites between 2005 and 2014. We compared differences in growth according to treatment approach over a 12-month period. Modification by sex and age was examined and sensitivity analyses were conducted to assess robustness of results given study assumptions. Results: In the 409 patients identified, the mean age and proportion male differed by treatment ( P  =  < 0.01 and P  = 0.04, respectively). Baseline growth measures were associated with slight impairment of height at diagnosis (median baseline height z score of −0.1 [interquartile range −0.9, 0.8]). In general, treatment approach was not associated with any significant increase or decrease in expected growth over a 12-month period. Subtle decrease in linear growth was observed with treatment using a combined elemental and topical steroid (Δ height z score [adjusted]: −0.04; 95% confidence interval [CI]: −0.08, −0.01). Differences in linear growth differed by sex ( P for interaction <0.01). For elemental formula in combination with topical steroids, only girls exhibited a significant decline in linear growth (Δ height z score [adjusted]: −0.24; 95% CI: −0.32, −0.17). A slight reduction in BMI was observed for patients treated with a combination of elemental diet and dietary elimination (Δ BMI z score [adjusted]: −0.07; 95% CI: −0.13, −0.01). Conclusions: Treatment of EoE, in general, is not associated with major anthropometric growth changes in most pediatric patients. Slight linear growth impairment was observed for topical steroid treatment, and sex differences in growth by treatment approach were observed. Future prospective studies should evaluate the effect of treatment on optimal growth and development and over a longer period of follow-up. Abstract : Supplemental Digital Content is available in the text